Religion, Ethics and Attitudes towards Corruption in Nigeria: A Historiographical Review (2011)
This study reviews the literature on corruption as it relates to religion in Nigeria. It explores corruption as a concept from its most popular usage to the official government position. It also explores the types and character of corruption and presents a historiography of the problem of corruption in colonial and postcolonial Nigeria. The ways corruption has been problematised in religious discourse, from the perspectives of African traditional religion, Christianity and Islam, paying attention to the transformations in these religions as they interact and influence one another and new religious movements are also examined. Additionally, it engages the debate on culture, religion, tradition and modernity in the dynamics of corruption in Nigeria. Further it engages the anti-corruption enterprise in Nigeria and the role of faith-based organisations in it. It argues that corruption in a heterogeneous and multi-religious post-colonial society like Nigeria must be conceived as a complex phenomenon that cannot be limited to a legal, political or economic concept. The concept goes beyond the idea of right and wrong, legal and illegal, socially acceptable or socially disapproved behaviour, abuse or misuse of power and touches on complex interactions through which we make sense of notions of good and evil. That is why it relates essentially to religion. Religion in Nigeria is, in the same vein a complex phenomenon of belief systems, not just in terms of people being exposed to multiple faith systems but also in terms of people espousing principles that straddle several religious opinions and beliefs that appear unlikely to sit together. The ways the apparent opposites mingle as people encounter social and material situations challenge us to adopt a methodology that is interpretative, sensitive to and grounded in empirical data in any engagement with religion and corruption